Immunoreactive corticotropin-releasing factor in human plasma. - Suda, T (1985)
Plasma immunoreactive corticotropin-releasing factor (I-CRF) levels were determined by using a human CRF radioimmunoassay and an immunoaffinity procedure. The basal plasma I-CRF level in normal subjects was 6 +/- 0.5 pg/ml (mean +/- SD). We found that most plasma I-CRF levels were affected by stress, negative feedback, and circadian rhythm. Basal I-CRF levels were high in patients with Addison's disease, Nelson's syndrome, hypopituitarism stemming from pituitary macroadenoma, and CRF- and adrenocorticotropic hormone-producing tumors. A very low, but significant, amount of I-CRF was detected (1-3 pg/ml) in patients with Cushing's syndrome, in corticosteroid-treated patients, and in a patient with hypothalamic hypopituitarism. These results suggest that a major component of plasma I-CRF is of hypothalamic origin, however, other extrahypothalamic tissues cannot be ruled out as a minor source of plasma I-CRF.